Spatial and interannual variations of seasonal sea surface temperature patterns in the Baltic Sea - Katarzyna Bradtke; Agnieszka Herman; Jacek A. Urbański (Oceanologia)
On the basis of monthly averaged satellite data, this study examined how the annual cycle of the Baltic Sea surface temperature (SST)varied spatially and temporally during the period 1986-2005.We conclude that there are two main thermal seasons in the Baltic Sea separated only by short transitional periods - spring lastingabout one month, and autumn lasting two months. Generally speaking, summer covers the part of the year from June to October withthe highest monthly mean SST in August. Winter, with a minimum monthly mean SST in February in shallow waters or in March indeeper areas, lasts from December to April. As a result of climate changes over the Baltic Sea region, strong positive trends inSST occur in the summer months. In consequence, the period with extremely high sea surface water temperatures has become slightlylonger in the central Baltic. In the last decade winter changes in SST display zero or even negative tendencies. The investigatedperiod was characterized by an annual increase in mean temperatures of about 0.03-0.07°C. However, the rates of monthlymean SST changes were sometimes more than three times as high.